The Impact of Later Life Events on Cessation Motivation of Older Adults with Substance Use Disorder in Hong Kong - Cheng, Vincent S. (International journal of offender therapy and comparative criminology, 2023)
Life-course researchers have found that age-graded life events, such as marriage and employment, may provoke a turning point in the trajectories of substance use and motivate young adults with substance use disorder (SUD) to seek addiction treatment and cease illegal drug use. However, few studies have focused on the impact of the life events experienced by older adults with SUD in their later life on these trajectories. Even less is known about this phenomenon in non-Western contexts. Thus, we conducted interviews with 34 older individuals with SUD in Hong Kong and explored how later life events affected their motivation to cease illegal drug use. Our findings highlight the influence of age on how life events are experienced and the need for age-specific academic studies of substance use trajectories. The results also have implications for policymakers, as the criminalization and stigmatization of drug use may have a negative impact on the trajectories of substance use among older populations.